Dimensi Spiritual dalam Psikoterapi:Dampak Praktik Sufi terhadap Kecemasan dan Depresi - Imroatul Husna; Khodijah (IAI Miftahul Ulum Pamekasan, 2024)
Mental disorders, such as anxiety and depression, have increasingly become a significant health issue in today's world, with various life pressures worsening these conditions. Traditional psychotherapy often fails to consider the spiritual aspects that can play a crucial role in the healing process. This study aims to examine how Sufi practices, such as dhikr (remembrance), muhasabah (self-reflection), and tawakal (trust in God), can be integrated into modern psychotherapy to help address anxiety and depression. Using a qualitative approach with case study and phenomenological methods, this research explores the experiences of individuals who have engaged in Sufi practices as part of psychological therapy. Participants were purposively selected based on the criteria of having experienced anxiety or depression, as well as having practiced Sufism for at least three months. Data were collected through in- depth interviews, observations, and personal documentation, which were then analyzed using thematic analysis techniques. The results of the study indicate that Sufi practices have a positive impact on reducing anxiety and depression, as well as improving inner peace and mental resilience. Integrating Sufism into psychotherapy offers a more comprehensive and holistic approach, which benefits not only the Muslim community but also anyone seeking healing through spirituality. This study also reveals the challenges and opportunities in applying Sufism in modern therapy.